Affect perception as a cognitive function: Validity and clinical application of a neuropsychological test battery in healthy individuals and patients with brain lesions - Χίου Καλλιόπη; Βάγια Αργυρώ; Χαριτίδου Ελένη; Καρακώστας Δημήτρης; Κοσμίδου Μαρία-Ελένη (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF